Current status of national regulations on tanning bed use and workers' protection from solar ultraviolet radiation: results from a global International League of Dermatological Societies (ILDS) questionnaire study - Bieck, Cara; Alberts, Antje; John, Swen Malte (Frontiers in Public Health, 2025)
IntroductionExposure to ultraviolet radiation (UVR) is the most important risk factor for the development of skin cancer. Outdoor workers and people who use tanning beds belong to the high-risk groups for developing this disease. The aim of the present study was to gather data about national regulations on the use of tanning beds and worker's protection from solar UVR.MethodsMember societies of the International League of Dermatological Societies (ILDS) were asked to participate in a survey by using standardized online questionnaires from January 2023 to January 2024.ResultsA total of 100 dermatologists from 66 different countries answered. Responses were pooled if more than one person responded for one country. Occupationally acquired skin cancer by solar UVR can be recognized as an occupational disease in 29 (43.9%) of 66 responding countries. In 29 (43.9%) of 66 responding countries there are legal instruments available aimed at controlling the cosmetic use of tanning beds. In 48 (72.7%) of 66 countries, the responding member society currently participates in any activities on UVR protection and/or use of tanning beds.DiscussionThe results of the presented study indicate a strong need for further action in terms of skin cancer prevention on different levels. This is of high importance due to the fact that skin cancer is a rapidly increasing global public health concern. This issue is particularly applicable to high-risk groups regarding the development of occupational skin cancer, as (a) outdoor workers as well as (b) people from the general population who may have limited awareness or understanding of UVR exposure risks (e.g., through tanning bed use).